Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1146/annurev-virology-093020-015957
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in Subsurface Environments

Abstract: Over the past 20 years, our knowledge of virus diversity and abundance in subsurface environments has expanded dramatically through application of quantitative metagenomic approaches. In most subsurface environments, viral diversity and abundance rival viral diversity and abundance observed in surface environments. Most of these viruses are uncharacterized in terms of their hosts and replication cycles. Analysis of accessory metabolic genes encoded by subsurface viruses indicates that they evolved to replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 148 publications
1
7
0
Order By: Relevance
“…As an important mechanism in adaptation to the environment, viruses can acquire new functional genes via transduction, i.e., auxiliary metabolic genes (AMGs) that contribute to host and/or viral fitness 4, 46 . Ten AMGs were identified in 7 viral genomes ( Figure 3d, Supplementary Figure 8 and Supplementary Table 9 ), related to four different types of functions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As an important mechanism in adaptation to the environment, viruses can acquire new functional genes via transduction, i.e., auxiliary metabolic genes (AMGs) that contribute to host and/or viral fitness 4, 46 . Ten AMGs were identified in 7 viral genomes ( Figure 3d, Supplementary Figure 8 and Supplementary Table 9 ), related to four different types of functions.…”
Section: Resultsmentioning
confidence: 99%
“…To date, studies of viral ecology and evolution have paid little attention to how subsurface viruses evolve to adjust to their surrounding environment and interact with their hosts 4,25,26,57 Together, these analyses of evolutionary dynamics of viruses will help guide future studies targeting the viral evolution and virus-host systems in extreme environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuous seepage of gaseous and liquid hydrocarbons boosts local biodiversity and microbial activity, featuring prevalent archaeal anaerobic methanotrophs (ANME) and sulfate-reducing bacteria (SRB) [ 1 , 2 ]. Compared to the rich knowledge of cold seep bacterial and archaeal communities, viruses remain largely underexplored in spite of their significant roles in impacting microbes and corresponding biogeochemical cycles [ 3 , 4 ]. Virus studies using enumeration or cultivation have shown that cold seep sediments are hotspots of viral production with high virus-prokaryote ratios [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%